IMPLEMENTASI NILAI-NILAI LUHUR AJARAN KI HAJAR DEWANTARA DALAM PERKULIAHAN PENDIDIKAN PANCASILA UNTUK MENGEMBANGKAN KARAKTER MAHASISWA - Ronggo Warsito; Sahid Teguh Widodo (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
This research aims are 1) to describe the implementation of the noble values of Ki Hajar Dewantara’s teaching to develop students' character, 2) to know the problems implementation of the noble values of Ki Hajar Dewantara’s teaching to develop students' character, and 3) find the strategy was implemented of the noble values of Ki Hajar Dewantara’s teaching to develop students' character. It used decriptive qualitative method with the single embedded case study strategy. The method data collection through in-depth interview, observation, documentation, and content analysis. Triangulation technique was used to check the validity. They were analyzed by using the interactive model. Conclusion: 1) the implementation of the noble values of Ki Hajar Dewantara’s teaching very important to develop the students’ character, 2) the problems implementation of the noble values of Ki Hajar Dewantara’s teaching from internal dan external factors, and 3) the strategy was implemented of the noble values of Ki Hajar Dewantara’s teaching to develop students' character with trilogi kepemimpinan.